Investigation on Household Medication-Taking Behavior and Affordability Among Patients Under Chronic Condition: A Survey Study in Gansu Province, China - Wang, Xiaohui; Zhang, Ming; Zhao, Shuaixiang; Lv, Meng; Li, Qinglin; He, Longjie; Hu, Ming (Frontiers in Pharmacology, 2020)
Aim: This study aimed to investigate the household medication-taking behavior and affordability of patients with chronic diseases in Gansu Province. As well as to propose suggestions to assist improvement of related policies. Methods: A multistage stratified cluster sampling technique was used to select the research sites and households according to the WHO manual for the “Household Survey to Measure Access and Use of Medicines”. The impact factors of medication-taking behavior were estimated using binary logistic regression models. Medication treatment affordability of hypertension patients was evaluated. Results: A total of 1080 completed questionnaires were collected, in which 690 families reported to have chronic patients in their home. The total number of chronic disease patients were 915. About 93% of the patient reported scheduled medicine intake. Approximately 86.60% of patients with chronic medical conditions were able to adhere to the physicians’ prescriptions. Age, gender, and the number of household chronic disease patients were the main factors influencing whether the patients take medication. Respondents’ self-reported monthly expenditure on household medicine accounted for 16.95% of their total monthly expenditure. The total cost of irbesartan and valsartan for hypertension treatment was two-fold higher than the minimum daily wage of the families. Conclusion: This study found that patients with chronic diseases have a high proportion of medication and medication compliance. However, family drug burden, especially for those living with hypertension are among the key challenges. Related policy needs to be revised to promote the affordability of medication under chronic conditions.